2022
DOI: 10.3390/electronics11101633
|View full text |Cite
|
Sign up to set email alerts
|

Measurement, Evaluation, and Control of Active Intelligent Gait Training Systems—Analysis of the Current State of the Art

Abstract: Gait recognition and rehabilitation has been a research hotspot in recent years due to its importance to medical care and elderly care. Active intelligent rehabilitation and assistance systems for lower limbs integrates mechanical design, sensing technology, intelligent control, and robotics technology, and is one of the effective ways to resolve the above problems. In this review, crucial technologies and typical prototypes of active intelligent rehabilitation and assistance systems for gait training are intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 104 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…As with other performance measures, accuracy can be defined as the ratio between correctly observed and wrongly observed movements to the total number of observed movements. Four studies among the identified studies used accuracy, in percentages, as the performance measure [ 50 , 52 , 57 , 63 , 75 ].…”
Section: Synthesis and Analysismentioning
confidence: 99%
“…As with other performance measures, accuracy can be defined as the ratio between correctly observed and wrongly observed movements to the total number of observed movements. Four studies among the identified studies used accuracy, in percentages, as the performance measure [ 50 , 52 , 57 , 63 , 75 ].…”
Section: Synthesis and Analysismentioning
confidence: 99%
“…The paper mainly focuses on the analysis and research of the cerebral blood oxygen signal in the system, and gradually extends the analysis and recognition method of the movement intention by using the cerebral blood oxygen signal to implement the actual brain-computer interface system. Some crucial technologies and typical prototypes of active intelligent rehabilitation and assistance systems for gait training are introduced in [2]. The limitations, challenges, and future directions, in terms of gait measurement and intention recognition, gait rehabilitation evaluation, and gait training control strategies, are also discussed.…”
mentioning
confidence: 99%